Challenges to implementing culturally specific models in juvenile corrections. Issue 2 (17th February 2017) - Feinstein, Rachel; Magidson, Mark
ABSTRACT: This research explores the challenges of implementing culturally specific models within juvenile corrections in the United States. In-depth interviews with 16 staff at a private correctional facility working with incarcerated youth revealed the barriers to recognizing cultural differences among juveniles, promoting an environment that prioritizes and encourages diversity, and creating a system of corrections that reflects the specific cultural needs of the incarcerated youth served. Such research highlights how the traditional framework of the U.S. criminal justice system is structured to favor white juveniles while failing to provide culturally specific models that address the needs of youth of color.